The Flaw in Formalist Accounts of Circumvention Tourism. Issue 3 (2022) - Shaw, Joshua
Abstract: Circumvention tourism is a form of medical tourism that occurs when individuals travel abroad to receive treatments that are a prohibited in their home county but permitted in a destination country. This paper explores this question: Should individuals be punished by their home countries for engaging in circumvention tourism? Guido Pennings, Richard Huxtable, and I. Glenn Cohen have all argued for what I call "formalist accounts" of circumvention tourism. That is, they try to show that certain types of circumvention tourism should or should not be punished in principle . Against them, I show that questions about circumvention tourism's punishability cannot be answered in the abstract. Whether individuals should be punished depends too much on the prima facie morality of the treatments being performed and the prohibitions being circumvented.